Analysis Of European Union Erasmus+ Sport Projects and Comparison of Turkey and Other European Countries - Serdar Ceyhun; Cemal Özman (Selcuk University, 2023)
The Erasmus+ Sport project is a European initiative that aims to support various aspects of sport development and inclusion. It covers a wide range of projects focussing on different areas in the field of sport. This study aims to analyse the Erasmus+ Sport projects funded by the European Union and to compare Turkey with other European countries. In our research, a document analysis research method was used. In the first period of Erasmus+ Sport projects, 874 sports projects between 2014 and 2020 were analysed. The data were obtained from the details and results page of the projects funded under the Erasmus+ programme of the European Union Commission. As a result of the document analyses, Italy was the coordinator of the most projects with 188 projects. Spain was the coordinator in 60 projects, Croatia 47, Greece 46, Bulgaria and France 45, Slovenia 40 and Romania 35. Turkey, on the other hand, ranked 18th with 18 projects. Among the institutions applying for projects, non-governmental organisations stand out with 407 projects, followed by universities, sports federations and sports clubs. According to the years, the highest number of projects was finalised in 2020 with 465 projects. A budget of 196,936,797 euros was allocated to 874 projects in total. Turkey has received project support worth 2.068.076 euros with 18 projects from this budget.